ANALISIS BENTUK ADOPSI INTERNATIONAL FINANCIAL REPORTING STANDARD (IFRS) DALAM KONTEKS INSTITUSIONAL (STUDI EMPIRIS 30 NEGARA BERKEMBANG PERIODE 2006 - 2015) - Rahmat Fajar Ramdani (Universitas Muhammadiyah Metro, 2017)
The purpose of this research is to analyzing adoption of international financial reporting standard in countries based on three institutional isomorphism perspective. This research used foreign aid as the proxy of coersive isomorphism and foreign direct investment and foreign portfolio investment, as the proxy of mimetic isomorphism, and the last to analyze normative isomorphism this research used educational quality as proxy. This research used 30 countries as the sample with ten years observation that start from 2006 to 2015. To analyze hyphotesis this research used logistic regression with SPSS version 23. This research find that foreign aid as the proxy of coersive isomorphism has a significant influence on the country's probability to fully adopting IFRS, then other result showed that educational quality as the proxy of normative isomorphism has a significant influence on the country's probability to fully adopting IFRS. This reseacrh did not show that foreign direct investment and foreign portfolio investment as the proxy of mimetic isomorphism has a significant influence on the country's probability to fully adopting IFRS. Keywords: Foreign aid, foreign direct investment, foreign portfolio investment, educational quality, IFRS adoption